Augmentation of power conversion efficiency of silicon photovoltaic cell utilizing poly(methyl methacrylate-co-acrylic acid) nanospheres encapsulated with silver or gold nanoparticles - Goh, Wee Sheng (2019)
Silicon solar cell is a promising candidate for the mass implementation of photovoltaic cell due to its well-developed fabrication processes, and the abundant availability as well as the non-toxicity nature of the raw material. Nevertheless, the high refractive index of silicon results in reflection losses of incident sunlight. Hence, efficient light trapping schemes must be implemented to suppress the optical losses. In this study, we demonstrate a novel approach by utilizing self-assembled poly(methyl methacrylate-co-acrylic acid), P(MMA-co-AA), polymer nanosphere arrays in addition to the incorporation of gold or silver nanoparticles as a light trapping layer to enhance the power conversion efficiency of the solar cells. The P(MMA-co-AA) nanospheres with diameters ranging between 100-160 nm were synthesized via emulsion polymerization. The particle size of the P(MMA-co-AA) nanospheres were determined by laser diffraction technique. The P(MMA-co-AA) nanospheres were characterized using infrared spectroscopy and exhaustive thermal analyses, namely differential scanning calorimetry and thermogravimetric analysis. The P(MMA-co-AA) copolymer exhibits a relatively high glass transition temperature which is in the range of 110-115°C and it has the main decomposition temperature at 395°C. The presence of the metallic nanoparticles iii in the polymer nanospheres was confirmed through transmission electron microscopy and energy dispersive X-ray technique. The surface morphology and topology of the arrays of polymer nanospheres on silicon substrates were characterized via field emission scanning electron microscopy and atomic force microscopy. By introducing the polymer nanospheres with an average diameter of 101 nm on silicon solar cells, a relative enhancement of 57% was observed under a AM 1.5 solar simulator, as compared to the bare solar cell with the efficiency of 2%. By incorporating gold nanoparticles (i.e. 3.75 × 10-3 wt%) and silver nanoparticles (i.e. 2.5 × 10-3 wt%) into the polymer nanospheres, the solar cells show further enhancement of 166% and 179% respectively.